ASSESSMENT OF SPEECH DEVELOPMENT IN SUBJECTS WITH PRELINGUAL HEARING IMPAIRMENT PRIOR TO OR AFTER COCHLEAR IMPLANTATION - Lazarovska, Vesna (Journal of Morphological Sciences, 2021)
Hearing is one of the most important features that every human being possesses, one of the five senses along with sight, smell, taste, and touch. This function is accomplished owing to the complex mechanism of the sensory organ for hearing, the ear, and its coordination with the nervous system. The impairment of the cochlear normal function, impairment of the transduction of the mechanical acoustic signal in the synaptic activity of the auditory nerve leads to disorders of the complex ear mechanism. The aim of this study was to evaluate the speech development, that is, to assess the speech-voice development by using the Test for recognition of simple questions in the period of 6, 12 and 24 months. The results of the test for development of hearing perception showed progression during the examined period. Subjects in whom cochlear implant was placed in the younger age showed better results at the Test for recognition of simple questions and they recognized the meaning of a larger number of questions. This was statistically confirmed with calculated correlations between the age when the intervention was realized and the number of perceived simple questions at 6, 12 and 24 months post-implantation. All three correlations were negative and statistically significant. Keywords : impaired hearing, cochlear implant, hearing perception, speech development https://doi.org/10.55302/JMS2141118l